Photodynamic Effects of Curcumin Against Cariogenic Pathogens - Araujo, Natalia Costa; Fontana, Carla Raquel [UNESP]; Bagnato, Vanderlei Salvador; Martinez Gerbi, Marleny Elizabeth (Mary Ann Liebert, Inc., 2012)
Background data: The presence of Streptococcus mutans and Lactobacillus acidophilus in dental structure is an indicator of a cariogenic biofilm. Photodynamic therapy is a technique that involves the activation of photosensitizers by light in the presence of oxygen, resulting in the production of reactive radicals capable of inducing cell death. Reduction of bacteria levels can provide additional means of preventing dental caries. Objective: The present study evaluated the susceptibility of planktonic cultures of S. mutans (ATCC 25175) and L. acidophilus (ATCC-IAL-523) from the Adolfo Lutz Institute (IAL) to photodynamic therapy after sensitization with curcumin and exposure to blue light at 450 nm. Methods: Bacterial suspensions of S. mutans and L. acidophilus isolated (as single species) and combined (multspecies) were prepared and then evaluated. Four different groups were analyzed: L-D- (control group), L-D+ (drug group), L+D- (light group), and L+D+ (photodynamic therapy group). Two different concentrations of curcumin were tested (0.75 and 1.5 g/L) associated with a 5.7 J/cm(2) light emission diode. Results: Significant decreases (p < 0.05) in the viability of S. mutans were only observed when the bacterial suspensions were exposed to both curcumin and light. Then, reductions in viability of up to 99.99% were observed when using 1.5 g/L of the photosensitizer. The susceptibility of L. acidophilus was considerably lower (21% and 37.6%) for both curcumin concentrations. Conclusions: Photodynamic therapy was found to be effective in reducing S. mutans and L. acidophilus on planktonic cultures. No significant reduction was found for L-D+, proving the absence of dark toxicity of the drug.